Molecular Cloning and Expression of the p25 Gene of Two Mexican Isolates of Citrus tristeza virus - Keremane Manjunath (Revista Mexicana de Fitopatología, 2002)
The p25 coat protein gene (CPG) of two mexican isolates of Citrus tristeza virus (CTV) was amplified by reverse transcription (RT) and polymerase chain reaction (PCR). The corresponding complementary DNA of the CPG for both CTV isolates was ligated to pET22b expression vectors and inserted into Escherichia coli BL21 competent cells. Transformed E. coli cells were further cultured in nutrient liquid medium and the expressed bacterial proteins were separated by SDS polyacrlylamide gel electrophoresis. Bacterial cultures transformed with the CPG expressed the recombinant coat protein (rCP) as a prominent protein band of about 26 and 28 kDa for the mexican CTV isolates MX8 and MX14, respectively. The corresponding bacterial culture of E. coli transformed with the T36 isolate used as positive control, showed a prominent protein band of about 26 kDa, and one more of ~25 kDa. Western blotting assays with polyclonal CTV specific antibodies showed a positive reaction with the rCP of the MX8, MX14, and T36 CTV isolates, respectively. Further electrophoresis runs followed by subsequent western blotting assays, showed a positive serological reaction with the expressed rCP for the MX8, MX 14, and T36 CTV isolates, and with the corresponding native coat protein present in crude sap of CTV infected citrus tissue. Sequence analysis of the amplified DNA for both isolates showed a fragment of 672 nucleotides in length, with a deduced aminoacid sequences of 223 residues long. There were no coincident nucleotides located at 52 different positions in the entire p25 gene between the mexican isolates that were reflected in nineteen distinct aminoacid residues located at different positions of the p25 gene. When the sequence analysis of the aminoacid residues for the two mexican CTV isolates was compared with available sequencing data for other CTV isolates from diverse geographical origin, the mexican MX8 isolate showed a close similarity with the group of CTV Florida mild T30, T26 and T55 CTV isolates, whereas, the MX14 CTV showed a close similarity with the B249 CTV isolate from Venezuela. Sequence analysis indicates the potential presence of stem pitting citrus tristeza virus isolates in Mexico.